(untitled) - MacLean, Alistair (Oxford, 2008)
On the Polar ice-cap, 640 kilometres north of the Arctic Circle, the deadly, icy winds can freeze a man to death in minutes. But the survivors of the crashed airliner are lucky -- they are rescued by three scientists from a nearby weather station. But why did the airliner crash in the first place? Who smashed the radio to pieces? And why does the dead pilot have a bullet hole in his back? The rescue quickly turns into a nightmare: a race through the endless Arctic night, a race against the time, cold, hunger -- and a killer with a gun.
Keywords: English language,Short stories,Tiếng Anh